1973
DOI: 10.1073/pnas.70.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Expression of the N Gene of Bacteriophage Lambda

Abstract: A quantitative assay for the N protein of bacteriophage X has been used to study the in vivo regulation of N gene expression. The assay makes use of the observation that in a cell-free protein-synthesizing system from Escherichia coli programmed with XN-DNA the X endolysin is made only if N protein is added to the reaction.The rate of synthesis of N protein in vivo is negatively controlled by the products of the CI and tof genes of the phage. Furthermore, N protein activity is extremely unstable in vivo. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Historically, N has been difficult to purify because of its folding of N could have an important regulatory role. Partial proteolysis would leave boxB RNA occupied by very short in vivo half-life ‫2ف(‬ min) (Schwartz, 1970;Greenblatt, 1973). Clearly, as a disordered protein, N is an amino-terminal N fragment, preventing the binding of functional N protein and, therefore, blocking antiter-an ideal target for the lon protease, which is the primary protease for misfolded proteins in E. coli (Gottesman, mination.…”
Section: Discussion Multiple Regions Of N Can Bind Rnapmentioning
confidence: 99%
“…Historically, N has been difficult to purify because of its folding of N could have an important regulatory role. Partial proteolysis would leave boxB RNA occupied by very short in vivo half-life ‫2ف(‬ min) (Schwartz, 1970;Greenblatt, 1973). Clearly, as a disordered protein, N is an amino-terminal N fragment, preventing the binding of functional N protein and, therefore, blocking antiter-an ideal target for the lon protease, which is the primary protease for misfolded proteins in E. coli (Gottesman, mination.…”
Section: Discussion Multiple Regions Of N Can Bind Rnapmentioning
confidence: 99%
“…Using an S30 transcription-translation system, Jack Greenblatt (working at Harvard at the time) demonstrated a requirement for N to synthesize endolysin from a DNA template (78). Using this assay, he showed that CI and Cro downregulated N expression (79). Furthermore, N itself was highly unstable (175 21 indicated another remarkable feature of the N reaction.…”
Section: The Story Of Nmentioning
confidence: 99%
“…These proteins are subjected to rapid degradation by various proteases, some of which are energy dependent (12). Among the proteins which are subjected to rapid degradation in E. coli are several proteins of bacteriophage X which regulate the life cycle of the phage (6,13,14,19,25,26). For example, the antitermination protein N of bacteriophage X is degraded by the product of the E. coli lon gene, which is an ATP-dependent protease (22).…”
mentioning
confidence: 99%